Animal viral diseases and global change: bluetongue and West Nile fever as paradigms - Jimenez-Clavero, Miguel Angel (Frontiers in Genetics, 2012)
Environmental changes have an undoubted influence on the appearance, distribution and evolution of infectious diseases, and notably on those transmitted by vectors. Global change refers to environmental changes arising from human activities affecting the fundamental mechanisms operating in the biosphere. This paper discusses the changes observed in recent times with regard to some important arboviral (arthropod-borne viral) diseases of animals, and the role global change could have played in these variations. Two of the most important arboviral diseases of animals, bluetongue and West Nile fever/encephalitis, have been selected as models. In both cases, in the last 15 years an important leap forward has been observed, which has lead to considering them emerging diseases in different parts of the world. Bluetongue, affecting domestic ruminants, has recently afflicted livestock in Europe in an unprecedented epizootic, causing enormous economic losses. West Nile fever/encephalitis affects wildlife (birds), domestic animals (equines) and humans, thus, beyond the economic consequences of its occurrence, as a zoonotic disease, it poses an important public health threat. West Nile virus has expanded in the last 12 years worldwide, and particularly in the Americas, where it first occurred in 1999, extending throughout the Americas relentlessly since then, causing a severe epidemic of disastrous consequences for public health, wildlife and livestock. In Europe, West Nile virus is known long time ago, but it is since the last years of the XXth century that its incidence has risen substantially. Circumstances such as global warming, changes in land use and water management, increase in travel, trade of animals, and others, can have an important influence in the observed changes in both diseases. The following question is raised: What is the contribution of global changes to the current increase of these diseases in the world?